Penerapan akuntansi manajemen lingkungan dalam pengelolaan limbah medis: studi kualitatif pada rumah sakit khusus daerah - Ropena, Hendry Dunand; Leiwakabessy, Theophilia Fina Febrione; Gainau, Paskanova Christi (Indonesian Indovisi Institute, 2025)
The development of hospital services has led to increased operational activities that potentially generate environmental impacts, particularly through the management of medical and non-medical waste. Environmental management accounting serves as an important instrument to ensure that these impacts are managed in an accountable and sustainable manner. This study aims to analyze the implementation of environmental management accounting at the Regional Specialized Hospital of Maluku Province by examining the processes of identification, recognition, measurement, presentation, and disclosure of environmental costs. The main issue addressed in this study lies in the gap between existing environmental management practices and accounting systems that have not yet explicitly represented environmental costs. This study employs a descriptive approach, with data collected through in-depth interviews with nine key informants, direct observation, and analysis of hospital financial documents. The findings indicate that environmental costs have been identified and allocated; however, they are still recorded on a cash basis, integrated into general operational expenses, and not specifically disclosed in financial statements. The implications of this study underscore the need to strengthen environmental management accounting systems to enhance transparency, accountability, and sustainability-oriented decision-making in the public healthcare sector.